Industrial Engineering: A Career in Phase with the World: Results of a First Survey of International Meetings by AACINI (AACINI - International Journal of Industrial Engineering, 2024)
In recent years, educational institutions have undergone multiple changes due to the perspectives of a global and local context that promote collaboration, linkage, and new modalities for managing and implementing education, aiming for increasingly better educational outcomes. The efforts for international linkage and spaces for articulation and joint growth have always been a genuine interest of the Argentine Association of Industrial Engineering and Related Careers (AACINI), which has been working as a non-profit Civil Association since its creation in 2011. During the COVID-19 pandemic, a joint research study was conducted by two faculties (Faculty of Exact Sciences, Engineering, and Surveying of the National University of Rosario and FRSN) in collaboration with AACINI to explore possible areas of opportunity and consult about the context and future projections.
Keywords: International Linkage; Industrial Engineering; Higher Education